Epidemiology of gradual-onset knee injuries in team ball-sports: A systematic review with meta-analysis of prevalence, incidence, and burden by sex, sport, age, and participation level - Chia, L.; Silva, D. O.; Whalan, M.; McKay, M. J.; Sullivan, J.; Fuller, C. W.; Pappas, E. (Journal of Science and Medicine in Sport, 2022)
Objectives:To systematically evaluate the literature and estimate the prevalence, incidence, and burden of gradual-onset knee injuries in team ball-sports. Design: Systematic review with meta-analysis. Methods: Six databases (MEDLINE, EMBASE, Web of Science, CINAHL, SPORTDiscus, SCOPUS) were searched from inception to June 2021. Cohort studies of team ball-sports reporting the number of gradual-onset knee injuries were included. Study quality was assessed using a modified Newcastle-Ottawa scale. Studies were pooled using a Freeman-Tukey Double arcsine transformation (prevalence) and a Poisson random effects regression model (incidence, burden). Results: Forty-nine studies that captured gradual-onset knee injuries (unclassified, patellofemoral pain, tendinopathies, and iliotibial band friction syndrome) across 15 team ball-sports were included. For unclassified gradual-onset knee injuries, prevalence was 4% (95% Confidence Interval (CI) 2% to 7%, I2=96%), incidence was 0.32 per 1000 player-hours (95% CI 0.25 to 0.43, I2=88%), and burden was 3.24 days lost per 1000 player-hours (95% CI 1.95 to 5.37, I2=99%). For patellofemoral pain, prevalence was 6% (95% CI 1% to 13%, I2=93%), and incidence was 0.07 per 1000 player-hours (95% CI 0.04 to 0.12, I2=67%). For tendinopathies, prevalence was 1% (95% CI 0% to 2%, I2=68%), incidence was 0.07 per 1000 player-hours (95% CI 0.04 to 0.11, I2=76%), and burden was 2.14 days lost per 1000 player-hours (95% CI 1.23 to 3.71, I2=92%). Conclusions Estimates of prevalence, incidence and burden generated from this systematic review quantify the extent of gradual-onset knee injuries in team ball-sports. Further research is required to assess whether age, sport, and participation level are predictors of gradual-onset knee injuries.